Glycerol hydrogenolysis over a Pt–Ni bimetallic catalyst with hydrogen generated in situ. Issue 61 (3rd August 2017) - Yan, Yuqiang; Zhang, Yiying; Jiang, Tao; Xiao, Tiancun; Edwards, Peter P.; Cao, Fahai
Abstract : Pt–Ni catalyst significantly promotes the conversion and selectivity of 1, 2-PDO due to a strong interaction between Pt and Ni. Abstract : Using hydrogen generated in situ from aqueous phase reforming provides an efficient and economic route for glycerol hydrogenolysis. A Pt–Ni bimetallic catalyst supported on γ-Al2 O3 has been prepared to catalyze the selective hydrogenolysis of glycerol to 1, 2-propanediol, with glycerol conversion reaching 71.4% in 3 h. The significant promotion of conversion and selectivity could be explained by the formation of Pt–Ni alloy based on catalyst characterization. The effects of Pt/Ni ratio, reaction temperature and reaction time on the conversion of glycerol as well as product selectivity were also investigated.